Effect of Implementing Sustainable Management Practices on Construction Claims Mitigation - Thabet, Zeina (2022)
The fragmented management of traditional construction projects, which mainly lacks the integration of project processes, often results in schedule delays and cost overruns leading to client dissatisfaction, quality defects, and increase in work accidents and injuries. As a result, claims and disputes are most likely to arise between the contracting parties that can be extremely expensive and may severely impact the project performance. Numerous studies have investigated the influence of integrating sustainable management practices (SMPs) in construction projects on specific project performance objectives, such as cost, time, and quality; however, none has considered the effect of implementing SMPs on claims and dispute resolution. This gave the impetus for this research which aims at studying the impact of implementing an integration of SMPs clusters on construction claims mitigation. To achieve this goal, a comprehensive literature review was conducted and resulted in the identification of 25 critical SMPs and 10 frequent construction claims. Then, a survey was designed and a total of 144 construction engineering industry experts participated to assess the effect of implementing the identified SMPs on claims mitigation. The received data was checked for reliability and then analyzed using Mean Score technique and factor analysis to identify major clusters of SMPs. Then, an adaptive neuro-fuzzy inference system (ANFIS) model was developed via MATLAB software, to establish optimal approaches for integrating SMPs that promote the reduction of different claim types. The research findings highlighted 12 optimal SMPs integrated approaches in eliminating different types of claims. Particularly, the research revealed that high implementation of three clusters of SMPs, namely “experienced green building certified professionals”, “sustainability requirements at early design phase”, and “sustainability requirements at execution phase” have the potential to eliminate or at least reduce the majority of construction claims. This study assists construction project management experts in identifying an optimal combination of a minimum number of sustainable management practices that, if implemented together, can help in significantly reducing targeted types of claims.